Is There Benefit in Identifying Asthma Triggers During an Exacerbation?. (February 2020) - James, Pushpom; Cornish, Anna; Brady, Kaylan; Morrison, Jennifer; Giunta, Yvonne; Zuckerman, Batya; Hahn, Barry
Introduction . Allergen-specific IgE (sIgE) testing provides an objective assessment of sensitization to an allergen. Goal . To identify the time when serum measurements of sIgE would be most sensitive. Methods . This was a prospective study conducted between September 1, 2015, and February 25, 2019. Subjects ≥5 and ≤18 years of age, seen in the ED or admitted with an asthma exacerbation, were tested for total IgE and 8 perennial sIgE levels. Subjects with elevated sIgE were tested again after symptom resolution. Results . A total of 104 subjects were enrolled; 50 subjects were eligible for inclusion in the analysis. There were statistically significant differences between the visits for all sIgE, except Alternaria alternatum. Conclusions . In pediatric patients, serum sIgE levels measured during an asthma exacerbation were elevated compared with when their asthma was in better control. sIgE testing during an asthma exacerbation may help identify asthma triggers, mitigate exposure, and hence improve asthma control.